Identification of fabrics and their properties by selected UP Diliman college students and fabric retailers - Geronimo, Apolinar Rex B.; Rayala, Maria Monica E. (Quezon City UP College of Home Economics, 2011)
ABSTRACT This study aimed to determine the capacity of selected students from the University of the Philippines-Diliman (UPD) and selected fabric retailers to identify fabrics and their properties. Objectives of the study determined if the selected respondents are able to identify selected fabrics in terms of fabric names, fiber type, type of weave and the fabrics' usage. Perception of the respondents on the properties of fabrics was also included in the objectives of the study. Quota or convenience sampling was used where thirty (30) respondents and five (5) fabric retailers were selected to participate in this study. This descriptive research used the quantitative method to analyze the knowledge and perception of the respondents. The researcher developed a questionnaire which included six fabric swatches including satin, canvas, velvet, denim, corduroy, and poplin. A checklist of fabric properties namely flexibility, extensibility, resilience, surface contour, surface friction and thermal character was given in the questionnaire. The results showed that most student respondents and selected fabric retailers are able to identify the correct names of the selected fabrics and the fabric's usage. However, most of the respondents are not able to correctly identify the type of fiber and type of weave. In the Perception Test, most of the respondents and fabric retailers are also not able to correctly measure the fabric properties of the selected fabrics. The study determined the importance of consumer education about the properties of fabrics. Fabric retailers must get more information from the suppliers so that they are able to educate the consumers.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Textile fabrics